Hubungan Tingkat Empati terhadap Tingkat Burnout Mahasiswa Kedokteran selama Pembelajaran dalam Jaringan di Fakultas Kedokteran Universitas Tanjungpura: Hasil Penelitian - Yudha Barri Akmal; Ita Armyanti; Sari Rahmayanti (PT Kalbe Farma Tbk., 2025)
Introduction: Distance or online learning conducted during the COVID-19 pandemic causes a lack of interaction among students which affects the level of empathy of these students. Online learning also causes stress in medical students which can lead to burnout. The purpose of this study was to determine the relationship between the level of empathy and the level of burnout among students of the Tanjungpura University Medical Study Program class of 2019. Methods: The method used in this research is an observational analytic study with a cross-sectional approach. The research population was students of the Tanjungpura University Medical Study Program class of 2019 who were taken using a sampling technique in the form of total sampling with a minimum sample size of 76 people. Bivariate analysis using Spearman correlation test. Results: The results obtained from the Spearman correlation test based on SPSS 24.0 analysis obtained a significance value of 0.768 (p>0.05) for the relationship between the level of empathy and the level of burnout. Conclusion: There is no relationship between the level of empathy and the level of burnout in students of the Medical Study Program at Tanjungpura University class 2019.